2017
DOI: 10.5535/arm.2017.41.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Sleep-Disordered Breathing in Subacute Phase of Stroke

Abstract: ObjectiveTo assess the frequency and severity of sleep-disordered breathing (SDB) in subacute stroke patients in Korea.MethodsWe consecutively enrolled subacute stroke patients who were transferred to the Department of Rehabilitation Medicine from February 2016 to August 2016. The inclusion criteria were as follows: diagnosis of the first onset of cerebral infarction or hemorrhage in the brain by computed tomography or magnetic resonance imaging; patients between 18 and 80 years old; and patients admitted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…According to Hermann et al, 60–70% of patients with stroke have SDB, which is much higher than that of the normal population [20]. Other studies have reported SDB in 50–70% of patients with acute and subacute stroke [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…According to Hermann et al, 60–70% of patients with stroke have SDB, which is much higher than that of the normal population [20]. Other studies have reported SDB in 50–70% of patients with acute and subacute stroke [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of SDB on participation during the acute/subacute stage of recovery poststroke was also mixed. One study 39 found that participants with SDB had significantly worse outcomes on measures of participation and 2 studies 39,44 found no difference in participation outcomes between participants with and without SDB. A HSATS was used to diagnose SDB in most of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies 35,36,38,39,[44][45][46][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] examined the impact of SDB on recovery after stroke. In these studies, there were a total of 1,998 participants, with a prevalence of SDB of 57.4%.…”
Section: Article Selectionmentioning
confidence: 99%
See 2 more Smart Citations